Problems of Indian religious women at midlife - Soreng, Agnes (Animo Repository, 1987)
The purpose of identifying the problems of religious women at midlife in the congregation of the Handlaids of Mary in India is to help the subjects become aware of their problems and to seek necessary help. Besides, the data collected may be a basis for the counselors, superiors, formators and spiritual directors to organize an on going formation program for the middle aged sisters. This study utilized the descriptive research design using the survey method and collecting the data through the questionnaire prepared by the researcher herself. The specific questions this study sought to answer were: 1. What are the problems of religious women at midlife in the following areas: a. Evangelical Counsels of chastity, poverty and obedience b. Community life c. Prayer life d. Apostolic life 2. What are the problems of religious women at midlife who belong to the: a. 34-45 age group and b. 46-55 age group in the different areas stated above? 3. What are the problems of religious women in the early adult age and old age when compared to those at midlife? 4. Is there a difference between five top ranking problems encountered by the religious women at midlife in the various areas of religious life when compared according to: a. age at entry into religious life: at an early age and at later age, b. present apostolate teaching, catechizing, nursing, social service and household-works, c. educational attainment: below high school, high school and training and college and above. The subjects consisted of 102 sisters from 15 different communities of the congregation of the Hand-maids of Mary in India. Their age ranged from 26-69.